Le microphone dans la balance : espaces et enjeux sonores des procès historiques des attentats de Paris et de Nice - Aurore Juvenelle (Criminocorpus)
The trials for the attacks of November 13, 2015 and the Nice attack of July 14, 2016 were held between September 2021 and December 2022, at the Île de la Cité courthouse in Paris. These historic terrorism trials have been described as "exceptional" given the unprecedented number of participants and the scale of the system put in place. This article initiates a reflection on the ways of listening to these trials under two aspects, first via a sound journey aimed at enlightening their daily reality in a sensitive way. It intertwines a ritualized relationship with a judicial space unusually fragmented by the security system, with the symbolism of a multi-secular monument where History is lived, day after day and over time, by a specific micro-society. Listening to these trials is then analyzing the sound as a central issue of a device aimed at ensuring the publicity of the proceedings to an exceptional number of actors, particularly the civil parties, inside and outside the courtroom. The microphone, which has become essential, nevertheless questions the principles of contradictory debate because the president has control over the distribution of the floor. Moreover, the judicial ritual is constrained by the need to remain fixed in front of the microphone. Finally, it is necessary to examine the stages of creation of the web radio, intended for civil parties, characterized in particular by a modification of the law and the code of criminal procedure.These first elements lay the foundations for a reflection on listening to historical terrorism trials without which the analysis of the content of the debates, which will be done elsewhere, would be biased.